Association of IL-6 and CRP gene polymorphisms with obesity and metabolic disorders in children and adolescents - PÂMELA F. TODENDI (Anais da Academia Brasileira de Ciências, 2015)
Activation of adipose tissue inflammation is associated with obesity caused by lipid accumulation in adipocytes. Through this activation, proinflammatory cytokines, such as Interleukin-6 (IL-6) and C-reactive protein (CRP) seem to influence metabolic disorders. The present study evaluated whether polymorphisms in the CRP (rs1205) and IL-6 (rs1800795, rs2069845) genes are associated with the development of metabolic disorders in children and adolescents. A cross-sectional study was performed, consisting of 470 students from the municipality of Santa Cruz do Sul, Brazil, aged 7-17 years. Body mass index (BMI) was classified according to overweight and obesity. Genotyping was performed by real-time Polymerase Chain Reaction (PCR). Anthropometric characteristics, biochemical markers, immunological markers and blood pressure were assessed. Descriptive statistics, chi-square and logistic regression were used for the analyses. No association was detected between the rs1800795 polymorphism and the assessed variables. Individuals with the risk genotype in the rs1205 gene were associated with the risk of developing hypercholesterolemia (OR 2.79; CI 1.40, 5.57; p = 0.003). Carriers of the risk genotype in the rs2069845 gene are associated with the risk of developing obesity (OR 3.07; CI 1.08, 8.72; p = 0.03). The polymorphism rs2069845 was associated with obesity and rs1205 was associated with the risk of developing hypercholesterolemia in Brazilian s choolchildren.